Efforts to Preserve the Siraman Gong Kyai Pradah Tradition in the Young Generation in the Disruptive Era - Yulia Widya Saputri; Bagus Setiawan (IAIN Madura, 2025)
The Siraman Gong Kyai Pradah Tradition is a form of local wisdom in Kalipang Village, Sutojayan District, Blitar Regency, which has high historical, social, and spiritual value. This tradition has experienced a decline in the participation of the younger generation along with the development of the times and the influence of globalization. This study aims to describe the role of historical values ​​in increasing the awareness of the younger generation towards preserving traditions, analyzing preservation efforts made by various parties, and describing the responses of the younger generation to the tradition. This study uses a qualitative approach with a descriptive method. Data were obtained through interviews, observations, and documentation of various informants, including caretakers, community leaders, village officials, and the younger generation. Data analysis was carried out through the process of condensation, presentation, and drawing conclusions and verification. The results of the study show that historical values ​​have an important role in fostering cultural awareness of the younger generation. Preservation efforts are carried out through cultural education, active involvement of the younger generation in traditional events, and support from the government and the community. Despite challenges such as rational thinking and lack of interest from the younger generation, this tradition still survives thanks to community solidarity and awareness of the importance of preserving local culture.